Dislodgment Resistance, Adhesive Pattern, and Dentinal Tubule Penetration of a Novel Experimental Algin Biopolymer-Incorporated Bioceramic-Based Root Canal Sealer - Galvin Sim Siang, Lin; Norhayati, Luddin; Huwaina, Abd Ghani; Josephine Lai, Chang Hui; Noorani, Tahir Yusuf (MDPI, 2023)
The currently available bioceramic-based sealers still demonstrate low bond strength with a poor seal in root canal despite desirable biological properties. Hence, the present study aimed to determine the dislodgment resistance, adhesive pattern, and dentinal tubule penetration of a novel experimental algin-incorporated bioactive glass 58S calcium silicate-based (Bio-G) sealer and compared it with commercialised bioceramic-based sealers. A total of 112 lower premolars were instrumented to size 30. Four groups (n = 16) were assigned for the dislodgment resistance test: control, gutta-percha + Bio-G, gutta-percha + BioRoot RCS, and gutta-percha + iRoot SP, with exclusion of the control group in adhesive pattern and dentinal tubule penetration tests. Obturation was done, and teeth were placed in an incubator to allow sealer setting. For the dentinal tubule penetration test, sealers were mixed with 0.1% of rhodamine B dye. Subsequently, teeth were cut into a 1 mm-thick cross section at 5 mm and 10 mm levels from the root apex, respectively. Push-out bond strength, adhesive pattern, and dentinal tubule penetration tests were performed. Bio-G showed the highest mean push-out bond strength (p < 0.05), while iRoot SP showed the greatest sealer penetration (p < 0.05). Bio-G demonstrated more favourable adhesive patterns. No significant association was noted between dislodgment resistance and dentinal tubule penetration (p > 0.05).